Role of adrenoceptors in the regulation of dopamine/DARPP-32 signaling in neostriatal neurons - Hara, Masato (2010)
Studies in animal models of Parkinson's disease have revealed that degeneration of noradrenaline neurons is involved in the motor deficits. Several types of adrenoceptors are highly expressed in neostriatal neurons. However, the selective actions of these receptors on striatal signaling pathways have not been characterized. In this study, we investigated the role of adrenoceptors in the regulation of dopamine/DARPP-32 signaling by analyzing DARPP-32 phosphorylation at Thr34 (PKA-site) in mouse neostriatal slices. Activation of β(1)-adrenoceptors induced a rapid and transient increase in DARPP-32 phosphorylation. Activation of α(2)-adrenoceptors also induced a rapid and transient increase in DARPP-32 phosphorylation, which subsequently decreased below basal levels. In addition, activation of α(2)-adrenoceptors attenuated, and blockade of α(2)-adrenoceptors enhanced dopamine D1 and adenosine A(2A) receptor/DARPP-32 signaling. Chemical lesioning of noradrenergic neurons mimicked the effects of α(2)-adrenoceptor blockade. Under conditions of α(2)-adrenoceptor blockade, the dopamine D(2) receptor-induced decrease in DARPP-32 phosphorylation was attenuated. Our data demonstrate that β(1)- and α(2)-adrenoceptors regulate DARPP-32 phosphorylation in neostriatal neurons. G(i) activation by α(2)-adrenoceptors antagonizes G(s)/PKA signaling mediated by D(1) and A(2A) receptors in striatonigral and striatopallidal neurons, respectively, and thereby enhances D(2) receptor/G(i) signaling in striatopallidal neurons. α(2)-adrenoceptors may therefore be a therapeutic target for the treatment of Parkinson's disease.